2021
DOI: 10.1007/s11356-021-16726-w
|View full text |Cite
|
Sign up to set email alerts
|

Unboxing the molecular modalities of mutagens in cancer

Abstract: Graphical abstract The etiology of the majority of human cancers is associated with a myriad of environmental causes, including physical, chemical, and biological factors. DNA damage induced by such mutagens is the initial step in the process of carcinogenesis resulting in the accumulation of mutations. Mutational events are considered the major triggers for introducing genetic and epigenetic insults such as DNA crosslinks, single- and double-strand DNA breaks, formation of DNA adducts, mismatched b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 508 publications
(489 reference statements)
0
25
0
Order By: Relevance
“…Patients with a co-mutation in multiple DDR pathways demonstrate a good response to ICIs [59,74]. HRR-MMR, or co-mutation in the HRR-BER pathway, is regarded as a potential biomarker [74][75][76]. In a study on pembrolizumab, 11 of 34 non-small cell lung cancer (NSCLC) patients were assigned to the co-mutation positive (co-mut+) group [74], in which ORR was 63.6% compared with 21.7% of the co-mutation negative (co-mut-) group.…”
Section: The Effect Of Altered Ddr Pathway Interactions On Icismentioning
confidence: 99%
“…Patients with a co-mutation in multiple DDR pathways demonstrate a good response to ICIs [59,74]. HRR-MMR, or co-mutation in the HRR-BER pathway, is regarded as a potential biomarker [74][75][76]. In a study on pembrolizumab, 11 of 34 non-small cell lung cancer (NSCLC) patients were assigned to the co-mutation positive (co-mut+) group [74], in which ORR was 63.6% compared with 21.7% of the co-mutation negative (co-mut-) group.…”
Section: The Effect Of Altered Ddr Pathway Interactions On Icismentioning
confidence: 99%
“…Epidemiological studies suggest that chronic inflammation may be linked to 15–20% of cancer deaths worldwide ( 30 , 31 ). Hence, the concept that virus-induced inflammation promotes tumorigenesis is not novel.…”
Section: Discussionmentioning
confidence: 99%
“…7 AFBO is a highly reactive and unstable AFB 1 metabolite that reacts with cellular macromolecules, including genetic materials-DNA, RNA, proteins, and membrane lipids, mediating lipid peroxidation (LPO) and cell damage. 8 Primarily, AFB 1 is hepatotoxic, yet, AFB 1 equally affects the reproductive system. Prior animal studies have revealed that sublethal doses of AFB 1 cause testicular degeneration.…”
Section: Impact Statementmentioning
confidence: 99%
“…7 AFBO is a highly reactive and unstable AFB 1 metabolite that reacts with cellular macromolecules, including genetic materials—DNA, RNA, proteins, and membrane lipids, mediating lipid peroxidation (LPO) and cell damage. 8…”
Section: Introductionmentioning
confidence: 99%